2022
DOI: 10.1002/pbc.30029
|View full text |Cite
|
Sign up to set email alerts
|

Safety and outcome of ultrasound‐guided tunneled central venous catheter in children with cancers from low middle‐income country: A prospective study

Abstract: Background: Central venous access devices (CVAD) are vital for cancer therapeutics in pediatric oncology. Tunneled vascular access devices (TVAD) are preferred in children for prolonged and frequent vascular access. Data on insertion, care, and complications of CVAD in children from low middle-income countries (LMIC) are scarce, heterogeneous, and retrospective. Procedure: This prospective observational study on eligible children <12 years with pediatric malignancies requiring chemotherapy for minimum 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…that ultrasound-guided central venous catheterization can reduce the incidence of catheter-related bloodstream infection [28][29] . However, Khera S [30] suggested that ultrasound-guided central vein catheterization was not associated with catheter-associated bloodstream infection. Buetti [31] believes that improper ultrasound procedures can increase the incidence of catheter-associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…that ultrasound-guided central venous catheterization can reduce the incidence of catheter-related bloodstream infection [28][29] . However, Khera S [30] suggested that ultrasound-guided central vein catheterization was not associated with catheter-associated bloodstream infection. Buetti [31] believes that improper ultrasound procedures can increase the incidence of catheter-associated infections.…”
Section: Discussionmentioning
confidence: 99%